Wave-Breaking Phenomena and Existence of Peakons for a Generalized Compressible Elastic-Rod Equation - Xiaolian Ai; Lingyu Jiang; Ting Yi (Abstract and Applied Analysis)
Consideration in this paper is the Cauchy problem of a generalized hyperelastic-rod wave equation. We first derive a wave-breaking mechanism for strong solutions, which occurs in finite time for certain initial profiles. In addition, we determine the existence of some new peaked solitary wave solutions.